Students’ perceptions regarding the use of Duolingo to enhance grammar learning - Fanni, Syandi Mei; Maharani, Mega Mulianing (CV. Yudhistt Fateeh, 2024)
English grammar is still particularly challenging for EFL students; a language learning application like Duolingo, provides interactive exercises with gamified elements. While many studies emphasize the role of technology in language education, research on students’ perceptions of using specific applications like Duolingo for grammar learning remains limited. Duolingo is widely praised for its interactive learning approach; there is a disconnect between its theoretical promise to enhance grammar skills and its practical effectiveness in this area, with some users reporting limited progress in grammar compared to other language components. This study investigated students’ perceptions of using Duolingo to enhance English grammar learning through a descriptive qualitative approach, utilizing semi-structured interview with 15 students. Data were collected through a face-to-face interview. The findings revealed that students perceive Duolingo as an engaging and flexible tool to enhance grammar learning due to its gamification features and accessibility. Duolingo effectively supported basic grammar comprehension and motivated learners to engage in learning actively. However, students highlighted limitations, including the lack of in-depth explanations for complex grammar rules and challenges such as technical issues and pressure from the grading system. While Duolingo was viewed as a complementary tool, students emphasized integrating it with conventional classroom instruction to enhance comprehension through direct interaction and feedback. These findings suggest combining Duolingo with face-to-face instruction could provide a more balanced and practical approach to grammar learning.